2020
DOI: 10.1051/e3sconf/202015101061
|View full text |Cite
|
Sign up to set email alerts
|

Non-Invasive Measurement of Cortisol Metabolite in Feces of Toraya Buffalo by Using Enzyme Immunoassay Technique

Abstract: Non-invasive measurement hormones in feces using enzyme immunoassay (EIA) technique needs to be validated. This study was conducted to develop and validate an enzyme immunoassay kit for measuring the concentration of cortisol metabolites in feces of Toraya buffalo. An EIA kit of 11β-hydroxyetiocholanolone (11β-hydroxy-CM assay) was developed and validated analytically and biologically using feces of Toraya Buffalo for cortisol metabolite measurements. Analytical validation comprises the parallelism test, accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
1
3
0
1
Order By: Relevance
“…This is because the 2 nd to 5 th week of observation is the school holidays. This result in line with a study that reported one of the factors of visitor attendance is a school holiday [15]. The sex of visitors is 51% male and 49% female which they visited the Sambar deer with a family group.…”
Section: Effect Of Visitor Numbers On the Cortisol Metabolite Concentrationssupporting
confidence: 90%
“…This is because the 2 nd to 5 th week of observation is the school holidays. This result in line with a study that reported one of the factors of visitor attendance is a school holiday [15]. The sex of visitors is 51% male and 49% female which they visited the Sambar deer with a family group.…”
Section: Effect Of Visitor Numbers On the Cortisol Metabolite Concentrationssupporting
confidence: 90%
“…The mean cortisol levels (ng/g) recorded before versus after transplantation on days 3, 5, and 7 were 146. 23 In this study, the transplant procedure was considered to be successful because some follicles remained in the various stages of development. This is in accordance with the report of Sumarmin et al [38], who stated that the success of the transplantation can be proved by the discovery of follicles; in fact, the presence of follicles proves that the epithelial structure that protects the ovarian cortex is intact, thus ensuring that metabolism can occur normally.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal samples were extracted using a method described by Gholib et al . [ 23 ]. Before the extraction process, all frozen fecal samples were thawed at 50°C for 1–2 h. Then, the samples were homogenized and ~0.55 g of the fresh fecal samples was placed in tubes containing 4.5 mL of 80% methanol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampel feses diekstraksi menggunakan metode seperti yang dilaporkan Gholib et al (2020). Tahap pertama sampel di-thawing pada suhu 50°C selama 1-2 jam.…”
Section: Ekstraksi Sampel Fesesunclassified